VIRULENCE OF Xanthomonas oryzae pv. oryzae AND REACTION OF RICE GENOTYPES TO THE RACES OFTHE PATHOGEN [Vimlensi Xanthomonas oryzae pv. oryzae dan Reaksi Genotipe Padi Terhadap Ras Patogen] - Suryadi, Y; Kadir, Triny S (Research Center for Biology-Indonesian Institute of Sciences, 2010)
The objective of the trials is to study host-pathogen relationships under green house test and field experiment.The virulence of Xanthomonas oryzae pv. oryzae (XOO) isolates of races III, and VIII is characterized on rice genotypes with different resistance to bacterial blight (BB) disease. The result shows that the multiplication of the bacterial population on the resistant (IR 36) and susceptible (TN-1) rice genotype is almost similar at initial Aage of infection; however, BB symptom expression as indicated by lesion length and area under disease progress curve (AUDPC) are much faster on TN-1 than that on IR 36 genotype. Based on rice field trial in Pusakanagara Expt. St; W. Java; almost all rice genotypes tested shows susceptible (S) to highly susceptible (HS) against XOO race VIII at generative stage observation.